PENERAPAN TEKNIK SHAPING UNTUK MENINGKATKAN DURASI PERILAKU ON-TASK ANAK DENGAN MASALAH ATENSI - Chairunnisa, Rahmatika Septina; Kemala, Cut Nurul (JURNAL PSIKOLOGI INSIGHT, 2020)
The aim of this study was to examine the effectiveness of the application of shaping technique with positive reinforcement, prompting, and fading technique in increasing the duration of on task-behavior in children with attention problem. The participant was AR, a 6- year-1-month-old boy who showed some behavior criteria or description of attentional disorder in interactive disorder category (ICDL-DMIC, 2005). The design in this study was a single-subject design with A-B type. The observer used a continuous recording method to measure the duration of on-task and off-task behavior when the child was working on some grade-1-level academic tasks. The result showed longer on-task behavior duration at the end of the intervention program.